A PERCEPÇÃO DO PACIENTE SOBRE PROCEDIMENTOS CIRÚRGICOS: INTERFACES ENTRE LINGUAGEM E SAÚDE - JABBOUR, Vitor; MACIEL, Ruberval Franco; FERNANDES, André Luis Marcondes; SILVA, Izabella Cristina; THEODOROVITZ, Armando Tomaz; PALOMARES, Danielly Larissa Pereira (ANAIS DO ENIC, 2023)
-